A New Measure of the Perceived Influence of Sexually Explicit Online Media on the Sexual Behaviors of Men Who Have Sex With Men. Issue 4 (3rd May 2016) - Nelson, Kimberly M.; Pantalone, David W.; Gamarel, Kristi E.; Simoni, Jane M.
Abstract : Men who have sex with men (MSM) frequently consume sexually explicit online media (SEOM), yet little is known about its influence on their sexual behaviors. We describe a sequence of four studies to develop and psychometrically validate a measure of the perceived influence of sexually explicit online media (PI-SEOM) on the sexual behaviors of MSM. Study 1 involved qualitative interviews ( N  = 28) and a quantitative survey ( N  = 100) to develop a preliminary measure. Using an Internet sample of MSM ( N  = 1, 170), we assessed its factor structure and reliability in Studies 2 and 3 as well as convergent validity and associations with HIV-related sexual risk in Study 4. Based on findings the measure was divided into two subscales: influences on (1) self and (2) other MSM. Factor analyses confirmed a two-factor model for each subscale, measuring perceived influences on (a) general sexual scripts and (b) condomless sex scripts. Survey results indicated that the more men perceived SEOM influencing their own condomless sex scripts, the more likely they were to report engaging in sexual risk behaviors. The developed measure holds promise for assessing the influence of SEOM on the sexual behaviors of MSM and may prove useful for HIV-prevention research.